2020
DOI: 10.21203/rs.3.rs-27928/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Listeria species, factors associated, and antibiogram of Listeria monocytogenes in beef at abattoirs, butchers, and restaurants of Ambo and Holeta Towns, Ethiopia

Abstract: Background Listeriosis is one of the globally distributed foodborne diseases with the highest fatality rate. Few studies were done on the occurrence of Listeria species from meat at abattoirs, butchers, and restaurants in Ethiopia, and there has been no study conducted at Ambo and Holeta town. The objectives of this study were to isolate and identify Listeria species, assess factors for contamination of meat, and antibiogram of Listeria monocytogenes along the meat chain in Ambo and Holeta towns, Central Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Studies from Iraq indicated that all strains were susceptible to meropenem, with varying susceptibility rates to cotrimoxazole (92.3%), ampicillin (84.6%), erythromycin (84.6%), and penicillin (69.2%) (19) suggesting regional differences in resistance pro les. Furthermore, our study found that 46.51% of isolates were resistant to more than three drugs, comparable to ndings by Gebremedhin and colleagues (22) in Ethiopia, where 100% of Listeria monocytogenes isolates showed resistance to two or more drugs, and 95% were multidrug-resistant. This highlights the challenge of multidrug resistance in treating Listeria infections, exacerbated by the misuse and over-the-counter availability of antibiotics.…”
Section: Description Of Factors Associated With Listeriosis Among Wom...supporting
confidence: 91%
See 1 more Smart Citation
“…Studies from Iraq indicated that all strains were susceptible to meropenem, with varying susceptibility rates to cotrimoxazole (92.3%), ampicillin (84.6%), erythromycin (84.6%), and penicillin (69.2%) (19) suggesting regional differences in resistance pro les. Furthermore, our study found that 46.51% of isolates were resistant to more than three drugs, comparable to ndings by Gebremedhin and colleagues (22) in Ethiopia, where 100% of Listeria monocytogenes isolates showed resistance to two or more drugs, and 95% were multidrug-resistant. This highlights the challenge of multidrug resistance in treating Listeria infections, exacerbated by the misuse and over-the-counter availability of antibiotics.…”
Section: Description Of Factors Associated With Listeriosis Among Wom...supporting
confidence: 91%
“…(17). However, our study's overall prevalence was lower than that reported in other studies, such as 20.83% in Iran (18), 31.1% in Iraq (19), 33.5% (20), 39.53% (21), 20.1% in Sub-Saharan Africa (Dufailu et al, 2021), and 28.44% in Ethiopia (22). Conversely, our study found a higher prevalence compared to studies in Iran (5.5% by Heidarzadehs and colleagues (23) and 3.66% by Ahmadi and colleagues (24)), 2.7% (25) in another meta-analysis study in Africa (5.17% by Geteneh and colleagues (26)), and 5.4% in Ethiopia (27).…”
Section: Prevalence Of Listeriosis Among Women With Spontaneous Abortioncontrasting
confidence: 82%
“…Nigeria [90], 2 (0.8) Reda Egypt [91], 5 (4.0) Turkey [92], 7 (2.9) Nigeria [93], 1 (0.5) Lybia [62], 12 (11.5) Nigeria [94], 4 (0.9) Ethiopia [95], 4 (0.9) ) Nigeria [96] Raw buffalo meat (0.9) Syria [110], 1 (0.5) Egypt [88], 1 (0.4) Iran [111], 1 (0.5) Turkey [112], 1 (1.6) Egypt [105], 12 (6) Egypt [113], 2 (0.8) Egypt [106], 3 (4.4) Turkey [114] Raw ewe milk 2 (0.2) Spain [115], 5 (0.9) Spain [116], 5 (0.6) Syria [110], 1 (0.4) Iran [111], 1 (1.6) Egypt [105], 1 (0.4) Egypt [106], 3 (0.9) Greece [117] Raw goat milk 3 (0.2) Spain [118], 4 (20) Egypt [119] Raw zebu milk 2 (1.9) Tanzania [120] Raw milk (animal species not detailed) 1 (0.6) Turkey [47], 1 (0.4) Italy [50], 1 (0.9) India [121], 1 (0.4) Turkey [54],…”
Section: Dairy Productsmentioning
confidence: 99%